Pengaruh Komunikasi Organisasi dalam Peningkatan Kinerja Usaha Kecil Menengah di Riau - musfiyaldi musfiyaldi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2013)
Although it has a central role in the national economy, The Small Management Economic (UKM-Usaha Kecil Menengah) has still not provide significant added value to economic development . This is due to limitations of SMEs in the procurement of technology ( communication technologies) , and low ability in management , as well as other limitations . Limitations and constraints faced by SMEs is still low productivity impacts generated and not a few have failed effort. In this paper, The process of organizational communication is the process of creating and exchanging messages in a tangle of relationships that depend on each other to cope with an uncertain environment or always changing conception affect the performance of the organization/company based on the idea that the company is a set of productive assets which include human resources, physical resources and capital to achieve a common goal. However, in this paper found that organizational communication has no significant effect on the performance of the business